(The Effect on The Quantity of Sulphuric Acid,Acetic Glacial and Aceton An The Production Terpineol From Alpa-Pinene) - Moestafa, Achmad; Waspodo, Priyo; -, Lucyana; Santosa, Budi (Warta Industri Hasil Pertanian, 1991)
Terpinol is one of the compounds which are terpene used as flavorand fragrance materials.In nature it is found in more than 200 derivatives from leaves,herbs and flowers.Syntheticaly it can be prepared from terpene hydrate which are derived from alpha-pinene trough its reaction with sulphuric acid,acetic glacialand aceton.It was observed that when alpha-pinene reacted with sulphuric acid,acetic glacial andaceton in 50:60:10 and 45 ratio,62% alpha-pinene was converted into alpha-terpineol.The contents of alpha-terpineol can also be observed from its refractives indexes and specific gravities,the higher the content had increased the values.